Association between cognition and cortisol in peri- and postmenopausal women - Karhula, Joonas (My University, 2023)
Cortisol is a steroid hormone that is responsible for homeostasis under stressful conditions. Although vital for survival, excessive cortisol has negative effects on physical and mental health in humans. The association between cortisol and cognition has been studied but the results remain inconsistent due to variations in study designs, study methods, and study populations. Area under curve (AUC) is commonly used in research to represent overall daily cortisol but no study has sampled cortisol during the night, or with more than 10 samples per day. Thus, AUC in literature does not completely represent daily cortisol and is inaccurate to the smaller changes in secretion. In this study, we used repeated cortisol sampling every 20 minutes to create circadian AUC, diurnal fall, and cortisol awakening response (CAR) values. For evaluation of cognitive function, a cognitive test battery with attention, memory, and visuospatial ability tests was used. The target population was 34 peri- and postmenopausal women. We found no association between circadian cortisol levels and cognition. Our AUC results demonstrated a more accurate measure for overall daily cortisol that also assessed smaller changes in secretion. Furthermore, we suggested that visual memory was associated with AUC only in younger population. Contradictory to the previous literature we showed no association between diurnal cortisol fall and cognitive test scores. Thus, we suggest that this difference is due to different populations in previous studies, and that when healthy non-demented elderly women are considered there is no association between diurnal fall and cognition.
Keywords: Cortisol, Cognition, Attention, Memory, Visuospatial abilities